2017
DOI: 10.1016/j.cjph.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic deviation equation in f(R, T) gravity

Abstract: In this paper, we investigate the modified Geodesic Deviation Equation (GDE) in the framework of f (R, T ) theory of gravity where R and T are the curvature scalar and the trace of the energymomentum tensor, respectively, using the FLRW background. In this way, we obtain the GR equivalent (GDE) in f (R, T ) metric formalism. We also extend our work to the generalization of the Mattig relation and perform the numerical analysis with GDE for null vector.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The f (R, T ) theory meets weak-field solar system conditions successfully, and new investigations make us able to assemble the galactic impacts of dark matter with the help of this theory [2]. It has also been found that f (R, T ) gravity shows clear tendency towards the deviation of the standard geodesic equation [3] and gravitational lensing [4]. Due to its viable nature, it can be applied to explore multiple astrophysical and cosmological phenomena, which can give rise to significant developments.…”
Section: Introductionmentioning
confidence: 87%
“…The f (R, T ) theory meets weak-field solar system conditions successfully, and new investigations make us able to assemble the galactic impacts of dark matter with the help of this theory [2]. It has also been found that f (R, T ) gravity shows clear tendency towards the deviation of the standard geodesic equation [3] and gravitational lensing [4]. Due to its viable nature, it can be applied to explore multiple astrophysical and cosmological phenomena, which can give rise to significant developments.…”
Section: Introductionmentioning
confidence: 87%
“…New terms from this theory allow us to portray the galactic impacts of dark matter [49]. It was also indicated that f (R, T ) gravity can give an extensive contribution to the deviation to the standard geodesic equation [50] and gravitational lensing [51]. This modified theory can be applied to investigate diverse issues of actual premium and may prompt some significant contrasts.…”
Section: Introductionmentioning
confidence: 99%
“…47 Also, the non-conservation of the energy-momentum tensor implies in non-geodesic motions for test particles in gravitational fields as it was deeply investigated. 48 In 49, 50 a different approach was considered. The authors have independently constructed a formalism in which an effective fluid is conserved in f (R, T ) gravity, rather than the usual energy-momentum tensor non-conservation.…”
Section: An Alternative Gravity With Extra Materials Termsmentioning
confidence: 99%